2021
DOI: 10.1177/03000605211017000
|View full text |Cite
|
Sign up to set email alerts
|

Addition of low-dose sufentanil to ropivacaine for reducing shivering and visceral traction pain during cesarean section

Abstract: Objective To investigate the efficacy of low-dose sufentanil for preventing shivering and visceral traction pain during cesarean section under spinal anesthesia. Methods This was a prospective, randomized, controlled study. A total of 112 full-term parturients who underwent elective caesarean delivery were randomly divided into two groups. Group R received 0.75% isobaric ropivacaine intrathecally and group RS received 0.75% isobaric ropivacaine plus 5 µg sufentanil intrathecally. Results There were no signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Previous studies have investigated the effect of applying a low dose of opioids (such as fentanyl) added to local anesthetics for neuraxial anesthesia, to enhance the neural block (23,24). Although anesthetic effect was improved, neuraxial opioids can also lead to serious side effects(7, 8), and parturients still didn't bene t from appropriate sedation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the effect of applying a low dose of opioids (such as fentanyl) added to local anesthetics for neuraxial anesthesia, to enhance the neural block (23,24). Although anesthetic effect was improved, neuraxial opioids can also lead to serious side effects(7, 8), and parturients still didn't bene t from appropriate sedation.…”
Section: Discussionmentioning
confidence: 99%
“…The initial shivering in the operating room was strongly associated with the labor analgesia, suggesting that the analgesics used during cesarean sections might induce shivering. Previous studies have reported that ropivacaine and lidocaine could increase shivering during cesarean sections [ 27 , 28 ]. Anesthesia may cause vasodilation, and cold disinfectant further promotes chills.…”
Section: Discussionmentioning
confidence: 99%
“…Intrathecal or epidural opioids have been reported to be effective in preventing visceral pain during cesarean sections. [7][8][9] However, adverse reactions like respiratory depression, urinary retention, nausea, vomiting, and itching limit their extensive use. 10 Esketamine, a dextrorotatory isomer of ketamine, is roughly twice as potent as ketamine.…”
Section: Introductionmentioning
confidence: 99%